2023
DOI: 10.1111/1346-8138.16747
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and comorbidity of hidradenitis suppurativa in Korea for 17 years: A nationwide population‐based cohort study

Abstract: Hidradenitis suppurativa (HS) is associated with various metabolic and autoimmune diseases. The epidemiology has been analyzed in various studies worldwide. However, epidemiological data on HS for Asian populations are limited. This study aimed to analyze the change in the prevalence and incidence of HS over 17 years in South Korea using the Korean National Health Insurance Service (NHIS) database. This study also evaluated the comorbidities in patients with HS. Population‐based data from the NHIS database of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…In a previous meta-analysis, despite the high heterogeneity in the existing evidence, the odds ratio for developing atopic dermatitis in HS patients was calculated to be 4.10 (95% CI, 2.16-8.18), whereas the odds ratio for asthma was 1.50 (95% CI, 1.24-1.81) 6 . In studies with a longitudinal design, a recent Korean study reported a 1.54-fold risk (95% CI, 1.47-1.61) for atopic dermatitis and a 1.21-fold risk (95% CI, 1.16-1.26) for asthma in HS patients 37 . The higher risk of atopic dermatitis in HS may be partially attributed to a potential genetic link between the two conditions, as suggested by a two-sample Mendelian randomization study 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous meta-analysis, despite the high heterogeneity in the existing evidence, the odds ratio for developing atopic dermatitis in HS patients was calculated to be 4.10 (95% CI, 2.16-8.18), whereas the odds ratio for asthma was 1.50 (95% CI, 1.24-1.81) 6 . In studies with a longitudinal design, a recent Korean study reported a 1.54-fold risk (95% CI, 1.47-1.61) for atopic dermatitis and a 1.21-fold risk (95% CI, 1.16-1.26) for asthma in HS patients 37 . The higher risk of atopic dermatitis in HS may be partially attributed to a potential genetic link between the two conditions, as suggested by a two-sample Mendelian randomization study 8 .…”
Section: Discussionmentioning
confidence: 99%
“…After the onset of the first symptoms, the diagnosis of HS still takes about 10 years on average, a fact that is important because the disease duration correlates with the number of comorbidities of respective patients [7]. Despite the regional differences, men appear to be as equally affected as women when viewed globally [8][9][10][11][12][13]. Given the great physical and mental burden of the disease, it is not surprising that HS patients have been found to show a considerable reduction in quality of life parameters, and this reduction is even more pronounced compared to other chronic inflammatory skin diseases, including psoriasis or atopic dermatitis [14].…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Nutrients 2023, 15, x FOR PEER REVIEW 2 of 30 appear to be as equally affected as women when viewed globally [8][9][10][11][12][13]. Given the great physical and mental burden of the disease, it is not surprising that HS patients have been found to show a considerable reduction in quality of life parameters, and this reduction is even more pronounced compared to other chronic inflammatory skin diseases, including psoriasis or atopic dermatitis [14].…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%